AWS architect associate certification exam prep. - Wilkins, Mark R. (O'Reilly Media, Inc., 2020)
Cloud computing is one of the most important and fastest growing sectors of the IT industry today. By providing companies and organizations of all sorts with the ability to offload expensive-to-maintain on-premises infrastructure to flexible and elastic managed services in the cloud, providers, led by Amazon Web Services (AWS), have profoundly reshaped the way IT organizations structure their data storage and compute strategies. Possessing the skills and expertise to work with AWS managed services is very much in demand, and one way to demonstrate your knowledge is by gaining certification through the AWS Certified Solutions Architect - Associate (CSAA) exam. In this video course, designed for IT technical professionals looking to make the move to the AWS cloud, host Mark Wilkins helps to prepare for the Managed Services portion of the CSAA exam. You'll begin by learning how to set up and manage a root user account. You then explore AWS concepts such as Identity and Access Management (IAM), creating managed databases, and setting up services such as autoscaling and Elastic Load Balancing (ELB). You'll examine connectivity options and look at monitoring services such as Amazon CloudWatch, and auditing services, including AWS CloudTrail. Mark explains these concepts and many more as well as provides demonstrations to help reinforce your learning. When you've completed this video course, you'll be well prepared to take the CSAA exam on AWS Managed Services and add that certification to your skill set. What you'll learn--and how you can apply it Setting up and managing root user accounts Understand administration and automation concepts for AWS Creating IAM users and groups Configuring multifactor authentication (MFA) and setting databases in AWS using RDS platforms and features Setting up and using CloudWatch and CloudTrail for monitoring and auditing How to design and add autoscaling and load balancers Understand how to deploy managed database solutions This video course is for you because... Your company is planning on, or is in the process of moving to the AWS cloud, and you need to prepare your staff or yourself to take the CSAA certification exam You want to design effective security controls using the IAM console You want to learn how to maintain deployed resources at AWS with built-in administrative tools You're a system administrator moving to AWS Prerequisites: You should have a technical background in networking, system administration, and working with virtualized resources You should possess a solid understanding of computing It would be beneficial to have a strong interest in advancing your skill set in cloud technology Materials or downloads needed in advance: Readings: PDF's AWS Managed Services.